USER SATISFACTION OF THE ZAKAT SYSTEM IN THE KEDAH STATE: FROM A QUALITY-IN-USE PERSPECTIVE (Journal of Digital System Development, 2025)
Lembaga Zakat Negeri Kedah (LZNK) has adopted two types of Zakat management systems: Jom Zakat and Zakat-on-Touch. The aim is to increase Zakat collection through online platforms. However, although Jom Zakat (adopted in 2018) and Zakat-on-Touch (adopted in 2019) have been in use for over five years, neither system has been evaluated from a Quality-in-Use perspective, which may impact user satisfaction. These evaluations are crucial to guarantee that the systems meet the necessary and established standards for quality in ISO/IEC 25010. Thus, the main objective of this study is to evaluate the Zakat systems’ user satisfaction from the Quality-in-Use perspective. The study was carried out in three stages using the quantitative approaches, involving literature reviews, instrument development, and survey distribution to 53 respondents. The data was analysed using SPSS. In general, the respondents are satisfied with the Quality-in-Use of the Zakat systems. The findings indicate that the study is highly significant by illustrating the correlations between User Satisfaction with Efficiency (mean=4.2, r=0.933, p=0.001) and effectiveness (mean=4.1, r=0.902, p